Record of an aberrant specimen of Tenualosa ilisha (Hamilton, 1822), from Narmada estuary - Vaisakh, G; Deshmukhe, G; Jaiswar, A K; Sahoo, A K; Das, B K (Journal of the Inland Fisheries Society of India, 2020)
Abnormality (or Anomaly) can be termed as any deviation from the normal body structure, either internally or externally (Gangan et al.,2018). Though reports on anomalies in fishes are common from confined conditions (Dawson and Heal, 1971), abnormalities among wild populations are infrequent or occasional (Valente, 1988). Several anomalies were reported in wild teleost fish populations in Indian waters mainly as deformities in vertebrae or skeletal abnormalities (Bapat and Radhakrishnan, 1966; Sen et al., 1991; Raj et al., 2004; Amitabh and Firoz, 2010; Sajeevan et al., 2014; Nagamuthu et al., 2015), deformities in internal organs (Thomas and Raju, 1964; Prabhakara Rao, 1969; Gupta, 1973; Anupkumar and Amitabha Ghosh, 1975), absence or deformities of fins (Kaushik, 1960; Gupta 1969; Nair, 1973; Babu Rao, 1975; Pandit and Dhanze, 2017; Gangan et al., 2018), etc. Present communication reports on the absence of ventral fins in a specimen of Tenualosa ilisha collected from Narmada estuary. It is the first report of an aberrant specimen of hilsa from an Inland water body.